Complete embolization of a mechanical aortic valve during trail running—a case report with a lucky ending. Issue 3 (2nd March 2022) - Dalen, Havard; Graven, Torbjørn; Slagsvold, Katrine H; Krogstad, Lars Erik; Saxhaug, Lars Mølgaard; Tannvik, Tomas D; Holte, Espen; Nordhaug, Dag Ole; Karlsen, Øystein; Thorstensen, Anders; Wahba, Alexander; Winnerkvist, Anders M
Abstract: Background: Complete embolization of a prosthetic heart valve is extremely rare and dangerous. This case reports a total embolization of a mechanical aortic valve and contributes to the literature regarding the diagnostic challenges related to infective endocarditis and follow-up after valvular surgery. Case summary: A 28-year-old male 11.5 years status-post a mechanical aortic valve replacement presented with acute onset of chest pain and dyspnoea while jogging. The patient lost consciousness and went into cardiopulmonary arrest with acute pulmonary oedema and circulatory shock. An echocardiogram revealed an empty aortic annulus, and a chest radiograph showed an embolized valve in the aortic arch. The patient underwent emergent removal of the embolized valve and replacement with a new mechanical aortic valve. The patient survived with minimal sequelae. At a 3-month follow-up, he had resumed work, and the only sequelae were mild left ventricular dysfunction and minor vision loss. Although he experienced no warning signs or symptoms, the most likely aetiology for embolization of the valvular prosthesis was infective endocarditis, which was revealed by re-evaluation of an echocardiogram recorded 1 month before the presentation which demonstrated a subtle motion abnormality of the valve. Conclusions: We present a case of a late complete embolization of a mechanical aortic valve most likely caused by asymptomatic infective endocarditis. The case illustrates the challenges in follow-up after valvular surgery and highlights the ultimate benefit of a well-functioning pre-hospital to hospital chain. Graphical Abstract: